Enzymatic surface hydrolysis of PET enhances bonding in PVC coating - Almansa, E. (2008)
The effect of polyesterase preparations from Thermomyces lanuginosus and Beauveria brongniartii on the hydrophilicity of PET materials was assessed. As a result of polyesterase treatment the hydrophilicity of PET fabrics was increased by up to 8 cm in terms of rising height with increases in surface tension from 6.2 mNm (heat-inactivated control samples) to above 8 mNm. Both enzymes were able to increase the amount of hydroxyl groups on PET from 90 to a maximum of 182 mmol kg-1, while only the B. brongniartii polyesterase released significant amounts of terephthalic acid from PET. Enzymatic surface hydrolysis of PET increased the bonding strength in PVC coating to 13.40 daN 5cm-1 using 0.5% adhesive compared to 11.5 daN 5cm-1 obtained without enzyme pretreatment and 6% of adhesive.